Pengaruh Motivasi Dan Kedisiplinan BelajarTerhadap Hasil Belajar Ipa Siswa Kelas TinggiDi Sd Muhammadiyah Alam Surya Mentari SurakartaTahun 2015/2016 - Wardhana, Adhityia; , Drs. Mulyadi S. K., SH.,M.Pd (2016)
Adhitya Wardhana/ A510120212. INFLUENCE OF MOTIVATION AND DISCIPLINE TO LEARN LEARNING OUTCOMES IN HIGH GRADE SD MUHAMMADIYAH ALAM SURYA MENTARI SURAKARTA 2015/2016. Thesis the Faculty of Education, University of Muhammadiyah Surakarta. June, 2016. The purpose of this study was to determine 1) the effect of learning motivation on learning outcomes of high-grade science students at SD Muhammadiyah ASM. 2)the effect of the discipline of learning the learning outcomes of high-grade science students at SD Muhammadiyah ASM. 3) the influence of motivation and discipline to learn the learning outcomes of high-grade science students at SD Muhammadiyah ASM. This research is a quantitative research. This study took place in SD Muhammadiyah ASM. The population in this study were students of class IV, V, and VI SD Muhammadiyah ASM taken as a sample of 30 students. The technique of taking the side by using simple random sampling. The technique of collecting data using questionnaires and documentation techniques. Data analysis technique used is multiple linear regression analysis. The conclusion of this study are 1) learning motivation positive and significant impact on learning outcomes of the IPA on the high grade students of SD Muhammadiyah ASM. Based on t test obtained t> t table, namely 3.604> 2.042 and the significance value <0.05 is 0.005 <0.05. Learn discipline and significant positive effect on the learning achievement in grade high IPA SD Muhammadiyah ASM. Based on t test obtained t> t table, namely 2.775> 2.042 and the significance value <0.05 is 0.010 <0.05. Learning motivation and discipline to learn together positive and significant impact on learning outcomes of the IPA on the high grade students of SD Muhammadiyah. Based on F test obtained Fhitung 27.822> F table 3.37, with a probability value 0.000 <0.05. Learning motivation variables contribute effectively 35,615%. Variable discipline of learning contribute effectively to 31,678%. By comparing the value of the effective contribution appears that learning motivation has a more dominant influence on learning achievement than the variable of learning motivation. Keywords: Learning Outcomes IPA, Motivation, Discipline Study.